THE EFFECT OF DASH DIET EDUCATION USING THE PEER GROUP METHOD ON THE EATING PATTERNS OF DIABETES MELLITUS PATIENTS IN KALIBUNTU VILLAGE - Wicaksono, Kurniawan Erman; Rahmat, Nafolion Nur; Purwanza, Sena Wahyu; Nurmawati, Ida; Hanifa, Salihati (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2025)
The management of diabetes mellitus (DM) includes diet management as an important  component  in  maintaining  blood  sugar  stability.  The  DASH  diet helps maintain electrolyte balance and cardiovascular health through calcium, potassium,  and  magnesium  intake.  Dietary  education  using  the  peer  group method  is  useful  for  sharing  experiences,  exchanging  information,  and providing and receiving emotional support.. This study aimed to determine the effect  of  DASH  diet  education  using  the  peer  group  method  on  the  eating patterns  of  Diabetes  Mellitus  (DM)  patients.  The  research  design  was  pre- experimental  with  a  one-group  pretest-posttest  approach.  The  study population consisted of 40 respondents, with a total sampling technique, and the data were analyzed using the Wilcoxon Sign Rank Test. After receiving DASH  diet  education,  most  patients  had  good  eating  patterns.  The  study results showed that DASH diet education using the peer group method had an effect on the eating patterns of Diabetes Mellitus patients. Based on the study findings,  it  was  expected  that  community  nurses  could  use  DASH  diet education interventions to improve blood sugar levels, lipid profiles, and blood pressure in diabetes mellitus patients.